Optimization of SIAP KAKA Application for the Implementation of the Tramtibum to the Community by the Pamong Praja Police Unit, North Kalimantan Province - Chendy Franklin Tan; Adyan Yanuar Ramadha; Selamet Dwi Purwantomo; Mujahidin (IHSA Institute, 2022)
The Civil Service Police Unit is a regional government apparatus in maintaining public order and peace and protecting the community as well as enforcing regional regulations and regional head regulations that take place dealing with the community. In helping to carry out these main tasks and functions, the Satpol PP of North Kalimantan Province made an application of the Strategy for Control of Public Order and Public Order (SIAP KAKA), the application (SIAP KAKA) is an application service whose job is to monitor conditions around areas/areas that are prone to Tramtibum violations via Circuit Closed Television (CCTV) based on Information Technology (IT) which is installed at various street corner points and at traffic lights. The purpose of this study was to determine the optimization of the SIAP KAKA application to facilitate supervision and control of the community by the Civil Service Police Unit of North Kalimantan Province. The method used in this scientific study is descriptive qualitative using a literature study approach, namely in collecting information and data, conducting a review of literature books and information from various internet. The results obtained show that the optimization of the SIAP KAKA application in supporting the implementation of the tasks and functions of the Satpol PP in Tramtibum is very easy and helpful, but there are still some obstacles that cause the SIAP KAKA application to not work properly, one of which is a budget problem.